Kielhofner's research in occupational therapy methods of inquiry for enhancing practice - Taylor, Renée R. 1970- (Philadelphia F.A. Davis, 2024)
Increased attention to qualitative ideology and methodology represents the major improvement in this third edition. Qualitative content has been moved to precede the quantitative content, and additional chapters that cover the hands-on application of qualitative methodology have been added. Moreover, all of the content in this text has been updated and improved to feature an increased number of examples and images of research-related tools, approaches, data collection, data analysis, and data outcomes work. The activities for learning also allow for direct application of chapter contents"--
Includes bibliographical references and index.
Keywords: Occupational Therapy; Research Design